2022
DOI: 10.3389/fpubh.2022.991350
|View full text |Cite
|
Sign up to set email alerts
|

A real-time driver fatigue identification method based on GA-GRNN

Abstract: It is of great practical and theoretical significance to identify driver fatigue state in real time and accurately and provide active safety warning in time. In this paper, a non-invasive and low-cost method of fatigue driving state identification based on genetic algorithm optimization of generalized regression neural network model is proposed. The specific work is as follows: (1) design simulated driving experiment and real driving experiment, determine the fatigue state of drivers according to the binary Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Therefore, it is demonstrated that it is feasible to use these parameters to identify these driving behaviors, and relevant methods are provided as technical support. For example, we have previously tried using cameras to identify driver fatigue [ 31 ] and distraction [ 32 ], which is the work conducted on the basis of our research and understanding of driving fatigue and driving distraction. This study is an exploratory study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is demonstrated that it is feasible to use these parameters to identify these driving behaviors, and relevant methods are provided as technical support. For example, we have previously tried using cameras to identify driver fatigue [ 31 ] and distraction [ 32 ], which is the work conducted on the basis of our research and understanding of driving fatigue and driving distraction. This study is an exploratory study.…”
Section: Discussionmentioning
confidence: 99%
“…The crossover rate of GA reached 0.8 (80%). Roulette wheel selection method was adopted to select individuals from the population for reproduction ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…AR-HUD technologies have aroused significant attention in the HCI field over the past few years. AR refers to a technology that superimposes computer-generated virtual objects onto the real world, creating a mixed reality environment where the virtual and physical worlds coexist HUD ( 12 ). Besides, it is a display technology that projects information onto a transparent screen or a windshield, such that users are enbaled to view information without looking away from the road or the task at hand ( 13 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations